Implementing a Strategy for Diagnostic Information from Dental and Panoramic Radiographs in Clinical Dentistry - Honda, Kazuya; Araki, Masao; Arai, Yoshinori (Shika Hoshasen, 2019)
General dentists in clinical dentistry need accurate diagnostic information from the radiographic investigations to plan dental treatment at the initial visit. Dental or panoramic images are used in the initial step for decide on the courses of treatment. Dental images mainly show the usefulness of paying a careful attention to detail under pathological condition, whereas the panoramic image provides clear information about the whole situation for pathological lesions in the oral-facial area. However, positioning of patient, radiographic condition, artifact, the directions of both rotational shooting and the shooting angle, and image interpretation in panoramic radiography all have a profound effect on diagnostic information obtained. When the radiologist is unclear in the interpretation and cannot provide a definite diagnosis, this presents a major challenge. Therefore, important points relating to interpretation of images are provided, in which radiologists consider the future strategy for dental and panoramic images. Our radiologists hope that readers will use this information and learn from the practical examples.